2016
DOI: 10.1159/000442133
|View full text |Cite
|
Sign up to set email alerts
|

Management of Regional Metastases of Malignant Salivary Gland Neoplasms

Abstract: Metastases from salivary gland carcinomas to the cervical lymph nodes are relatively uncommon. However, their impact on prognosis is significant and, thus, it is important to manage them appropriately. Treatment of clinically evident metastases consists primarily of surgery, frequently followed by radiation. Management of the N0 neck, on the other hand, remains controversial. While there seems to be agreement regarding the tumor and patient factors that make it more likely for a patient to harbor subclinical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…In contrast, immunotherapies aim at boosting the anti-tumor immune response of the tumor patient. While conventional cancer immunotherapy strategies so far have had only very limited success [ 6 ], immune checkpoint blockade therapies are very promising new approaches in cancer therapy [ 3 ], [ 4 ], [ 6 ], [ 7 ], [ 30 ], [ 31 ]. Such therapies are designed to restore the patients’ own antitumor immune response that had been mitigated during the processes of tumor immune evasion.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, immunotherapies aim at boosting the anti-tumor immune response of the tumor patient. While conventional cancer immunotherapy strategies so far have had only very limited success [ 6 ], immune checkpoint blockade therapies are very promising new approaches in cancer therapy [ 3 ], [ 4 ], [ 6 ], [ 7 ], [ 30 ], [ 31 ]. Such therapies are designed to restore the patients’ own antitumor immune response that had been mitigated during the processes of tumor immune evasion.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal management of these tumours remains controversial. As Medina et al [15] concluded in their review, given the contradictory data in the literature, the debate remains open. Medina et al discuss how beliefs about the optimal management of the neck have changed in recent decades [15].…”
Section: Discussionmentioning
confidence: 99%
“…As Medina et al [15] concluded in their review, given the contradictory data in the literature, the debate remains open. Medina et al discuss how beliefs about the optimal management of the neck have changed in recent decades [15]. In this regard, regrettably, the findings of our study cannot resolve the ongoing debate.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical lymph node metastasis is a negative prognostic factor in patients with salivary gland carcinoma, 1‐6 and therapeutic neck dissection (TND) is recommended in patients with clinically involved cervical lymph nodes 7‐12 . However, there are no universally accepted guidelines on the surgical treatment of patients with clinically negative neck.…”
Section: Introductionmentioning
confidence: 99%
“…Current practice in Denmark is TND in patients with clinically positive cervical lymph nodes, and elective neck dissection (END) is recommended in patients with T3/T4 tumors, high‐grade histology tumors, or in cases of facial nerve palsy 13 . This approach is supported by studies that recommend END in patients with high‐grade histology tumors or advanced tumor classifications 8,11,12,14‐21 . Other studies have recommended END in all patients with salivary gland carcinomas, 22‐26 because preoperative evaluations of histological tumor subtypes and grades are unreliable and there is a risk of regional metastases even for low‐grade histology tumors.…”
Section: Introductionmentioning
confidence: 99%